2019
DOI: 10.1128/jvi.01801-18
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of a Conserved Tyrosine in the Papillomavirus E2 Protein Regulates Brd4 Binding and Viral Replication

Abstract: The papillomavirus (PV) E2 protein coordinates viral transcription and genome replication. Following a strategy to identify amino acids in E2 that are posttranslationally modified, we reported that tyrosine kinase fibroblast growth factor receptor 3 (FGFR3) complexes with and phosphorylates E2, which inhibits viral DNA replication. Here, we present several lines of evidence indicating that tyrosine (Y) 138 of HPV-31 E2 is a substrate of FGFR3. The active form of FGFR3 bound to and phosphorylated the region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 60 publications
2
21
1
Order By: Relevance
“…Several serine/threonine phosphorylation sites have been identified in the papillomavirus protein E2 (3,5,6,28,29), but only two tyrosine phosphorylation sites have been examined: Y102 and Y138 (7,30). Phosphorylation at Y102 was originally identified in BPV-1 E2 through mass spectrometric analysis (7) and subsequently confirmed in the current work for HPV-31 E2.…”
Section: Discussionsupporting
confidence: 51%
“…Several serine/threonine phosphorylation sites have been identified in the papillomavirus protein E2 (3,5,6,28,29), but only two tyrosine phosphorylation sites have been examined: Y102 and Y138 (7,30). Phosphorylation at Y102 was originally identified in BPV-1 E2 through mass spectrometric analysis (7) and subsequently confirmed in the current work for HPV-31 E2.…”
Section: Discussionsupporting
confidence: 51%
“…HPV-31 genomes with the E2 Y138E phosphomimetic mutation were unable to maintain episomes in keratinocytes. We previously reported that the HPV-31 Y138E E2 protein did not bind to the Brd4 CTM but coimmunoprecipitated with full-length Brd4 (16). The Brd4 CTM has been shown to contact amino acids R37 and I73 within the TAD of E2 (24, 29-32).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies demonstrated that HPV-31 E2 with tyrosine 138 mutated to glutamate (Y138E) bound E1 and was capable of binding the ori yet was inactive for induction of E1-dependent transient DNA replication. Y138E did not form nuclear replication foci, and it bound to full-length Brd4 but did not associate with its CTM (16). Our transient-transfection DNA replication experiments utilized cytomegalovirus (CMV) promoter-driven E1 and E2 expression vectors with the HPV origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmids, siRNA, and Antibodies. The plasmids used were FLAG-SMC6/pcDNA3 (GenScript, Piscataway, NJ, USA), HPV-31 FLAG-E2/pcDNA3, HPV-31 FLAG-E2 mt (residues 205-372; [ 33 ]), HPV-31 V5-E2/pcDNA3, HPV-31 HA-E1/pcDNA3, and pcDNA3. The siRNA depletion of SMC5/6 subunits used siScramble DsiRNA (IDT; 51-01-19-08), siSMC6 (IDT; hs.Ri.SMC6.13.2), and siNSE3 (IDT; hs.Ri.NDNL2.13.1).…”
Section: Methodsmentioning
confidence: 99%